IMPLEMENTASI TEORI BELAJAR HUMANISTIK PADA MATA PELAJARAN AKIDAH AKHLAK DAN PENGARUHNYA PADA PERILAKU SISWA DI KELAS VIII MTS AL-AS’AD BRAMBANG DIWEK JOMBANG - Nur Ariska; Hidayatur Rohmah (JoEMS (Journal of Education and Management Studies), 2020)
This study aims to determine the student's behavior on the implementation of humanistic learning theory on the subjects of the Akhlak Creed in Mts Al-As'ad Brambang. To achieve that goal, researchers use data collection techniques through interviews, polls, and documentation. Data is processed using quantitative analysis to determine the implementation of humanistic learning theories on the influence of student behaviour. This research includes the type of field research that is the author doing research directly to the site to obtain and collect data. The results showed that the level of implementation of humanistic learning theory belongs to good category. The level of student behaviour is "adequate" and is reviewed from the average outcome of 69,75. The hypothesis test results show that the value of the Sig. (2. tailed) < 0.05 Then there is a correlation between the implementation of humanistic learning theory with student behavior is 0.000 < 0.05 which means there is a significant correlation. The effectiveness of the implementation of humanistic learning theory on the subjects of Akhlak in Mts Al-As'ad Brambang is still relatively high in the influence of student behaviour of 54%. From the hypothesis test and the Pearson Corelation calculation can be concluded that the implementation of the Humanistic learning theory is said to be quite effective and sufficient to affect student behaviour significantly.